Undang-undang Panji Selaten dan Beraja Niti tentang Hukum Islam di Kesultanan Kutai Kertanegara - Makmun Syar'i (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2010)
This paper discusses the problem of inter-marriage between customary law and Islamic law by referring to the laws of Panji Selaten and Beraji Niti as a case in point. These are the laws of Kutai Kertanegara Sultanate in Kalimantan. The paper particularly asks to what extent does customary law in Kutai Kertanegara absorbs Islamic law and vice versa. We argue that this case is a perfect example of not only the ability of Islam to adapt to a local scenario but also the genius of early Muslims in this particular region to understand the universal message of Islam. That Islam is universal means that it is applicable in different settings and contexts. We also discuss the history of the two laws, their characteristics and systems in order to present a clear idea of how they connote to the Islamic values. Further, through this study we try to show that in one way or another, the Dutch colonizing power at the time was aware that to keep the resistance at bay, it has to apply the policy of what Van Den Berg calls receptio in complexu, that is recognizing and applying Islamic law for the Muslims.